TOF SIMS analysis of fatty acid outgassing from wafer boxes adsorbed on wafers. (14th November 2014) - Gui, D.; Shao, J. J.; Hao, M.; Xing, Z. X.; Lee, H. S.; Shen, Y. Q.; Li, X. M.; Cha, L. Z.; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; et al.
<x xml:space="preserve">Abstract</x> Surface cleanness is crucial for reducing defect density of the semiconductor wafers. Organic contamination or residue on the wafer surface will lead to unintentional hydrophobization changes and haze formation and thus the performance of the subsequent wafer processes, such as film deposition or etching. Fatty acid salt is a common anionic surfactant. The residue of fatty acid salt will result in uneven etch of silicon and silicon nitride, which eventually causes particle issues. Time‐of‐flight SIMS was employed in this work to detect fatty acid residue on silicon, silicon oxide and silicon nitride wafers. The outgassing of the wafer container has been found to contribute to the fatty acid residue on the wafer surface. The outgassing of three different brands of wafer boxes was compared by investigating the adsorption on the wafers after fresh wafers were stored in boxes for a series of time duration. Different wafers also showed varied ability to absorb fatty acid, which can be attributed to electric dipole strength and concentration on the wafer surface. Time‐of‐flight SIMS and Fourier transform infrared spectroscopy analysis results showed that the difference in outgassing performance of different wafer boxes were due to the release agent residue on inner surface of the wafer boxes. More reliable results of fatty acid salt have been obtained on the wafers kept in the boxes with less outgassing. Copyright © 2014 John Wiley & Sons, Ltd.